Efficiency Optimization of One-Bit Full Adder through Quantum Dot Cellular Automata (International Journal of Scientific Research in Science and Technology, 2024)
In the present study, a view to keep MOS devices such as CMOS technology appropriates to “Moore’s Law” several solutions have been proposed. Despite those proposals, these solutions also face quite a few restrictions and constriction. This has boosted the research to discover alternative technologies, to design circuits at great nanometer level. In future the conventional digital system and circuit can be designed through Quantum Dot Cellular Automata. High density as well as rate is superior matches for QCA. The QCA are in the place of the digital circuit in order by division of electrons. It is gorgeous for its dense dimension, quicker velocity, extremely scalable, advanced switching frequency, and small power use compared to CMOS skill. QCA are emergent skill that is measured as the improved practical exchange resolution for CMOS skill which suffers from short channel effect. QCA is a transistor less technology which has charge skill, and the data is spread and framed on the electrons charge and by columbic interaction hypothesis. QCA can get more than CMOS skill in future because of its major profit. This paper mostly projects the realization and simulation results of various logic gates as: Majority Voter gate, Basic gate, Universal gate, Exclusive gate & Full Adder through QCA. All utilities and presentation of the schemes can be displayed through QCA Designer 2.0.
Keywords: Majority Voter; QCA; Logic Gates; Full Adder; Quantum